A clockwork fish: Age prediction using DNA methylation‐based biomarkers in the European seabass. (25th November 2019) - Anastasiadi, Dafni; Piferrer, Francesc
Abstract: Age‐related changes in DNA methylation do occur. Taking advantage of this, mammalian and avian epigenetic clocks have been constructed to predict age. In fish, studies on age‐related DNA methylation changes are scarce and no epigenetic clocks have been constructed. However, in fisheries and population dynamics studies there is a need for accurate estimation of age, something that is often impossible for some economically important species with the currently available methods. Here, we used the European sea bass, a marine fish the age of which can be determined with accuracy, to construct a piscine epigenetic clock, the first one in a cold‐blooded vertebrate. We used targeted bisulfite sequencing to amplify 48 CpGs from four genes in muscle samples and applied penalized regressions to predict age. We thus developed an age predictor in fish that is highly accurate (0.824) and precise (2.149 years). In juvenile fish, accelerated growth due to elevated temperatures had no effect on age prediction, indicating that the clock is able to predict the chronological age independently of environmentally‐driven perturbations. An epigenetic clock developed using muscle samples accurately predicted age in samples of testis but not ovaries, possibly reflecting the reproductive biology of fish. In conclusion, we report the development of the first piscine epigenetic clock, paving the way for similar studies in other species. Piscine epigenetic clocks should be of great utility for fisheries management and conservation purposes, where age determination is of crucial importance.